PENGARUH TEMPERATUR TUANG DENGAN JENIS MATERIAL PADUAN Al RONGSOK (KAMPAS REM PANCI) TERHADAP POROSITAS, KEKERASAN DAN STRUKTUR MIKRO HASIL PENGECORAN EVAPORATIVE - Syaiful Rahman; Rudi Siswanto (Scientific Journal of Mechanical Engineering Kinematika, 2019)
Recycling is a way of processing used materials that is started with selection, collection, then the process of foundry to create a new product that is more valuable economical. The objective of this research is to know the effect of casting temperature with the kind of guide material AI alloy junk from brake shoe and pan on porosity, hardness, microstructure (the evaporative foundry result). The recycling of used aluminum is an alternative to reduce the waste material from aluminum. Casting temperature is an variable that can effect the result of foundry where if the casting temperature is low, then there will be a quick freeze before the mold is completely filled. And if the casting temperature is too high, then shrinkage can occur and the porosity value may increase. This research used four casting temperature variations, namely: 650°C, 700°C, 750°C, and 800°C. The evaporative foundry method uses styrofoam pattern that is piled up into sand mold. The metal that is casted will form like styrofoam pattern. The result of casting temperature testing can effect on porosity, hardness, and microstructure.